Perancangan Pembangkit Listrik Tenaga Surya Sistem On-Grid di Atap Gedung untuk Memenuhi Kebutuhan Energi Listrik Fakultas Teknik Universitas Kristen Indonesia – Jakarta - Sitorus, Yofi Grecia; Widodo, Bambang; Purba, Robinson (Prodi Teknik Elektro FT UKI, 2022)
This research is the design of an On-Grid Solar Power Plant (PLTS), at the Faculty of Engineering building of Universitas Kristen Indonesia (FT UKI). In analysing this design, both from the technical and economic sides and determining the Break Event Point (BEP), the HOMER application tool is used. The research method used is quantitative method, which includes collecting, analysing and presenting data in the form of numbers. After doing the HOMER simulation. PLTS consists of 407 solar panels with a total overall power capacity of 150,890 Wp (watt peak), as well as 16 units of inverters with a total overall capacity of 160,000 kW (kilowatt), and the total cost of all components is Rp. 1,245,305,649.95. In terms of economics, the cost savings from the Net Present Cost (NPC) value of this design is Rp. 830,000,000, saving the Levelised Cost of Electricity (LCOE) cost of Rp. 227.87/kWh (kilowatt hour), and saving Operation & Maintenance (O&M) costs of Rp. 142,000,000. From the results of this study, a BEP value of around 7.27 years was obtained.